Systematic analysis of natural antibody responses to P. falciparum merozoite antigens by protein arrays - Fan, Yan-Ting; Wang, Yue; Ju, Chuan; Zhang, Ting; Xu, Bin; Hu, Wei; Chen, Jun-Hu (Journal of proteomics, 2013)
With the completion of the functional genome, merozoite proteome and stage-specific transcriptomes of the intraerythrocytic developmental cycle of Plasmoidum falciparum, the development of new vaccine candidates targeting Plasmodium merozoites is now possible. Here we report using protein array technology to detect antibody responses to Plasmodium merozoite proteins by screening the serum of Plasmodium-exposed individuals. A total of 138 genes encoding P. falciparum merozoite proteins were cloned using the In-Fusion cloning method and expressed using a wheat germ cell-free system (WGCF). These proteins were then screened with serum from Plasmodium-exposed individuals and unexposed subjects using protein arrays. A total of 30 highly immunoreactive merozoite antigens were identified (21.7% of 138 target proteins), including 10 well-characterized blood-stage vaccine candidates for P. falciparum. In addition, we report for the first time 7 proteins (MSP3.5, MRSP2, ETRAMP11.2, ETRAMP14.1 and RALP1, and two hypothetical proteins PFA0210c and PF14_0572) as being immunologically reactive. These novel Plasmodium merozoite antigens may be potential vaccine candidates for blood-stage malaria, and warrant further study. [Display omitted] ► Protein arrays were applied to screen the Ab responses to Pf merozoite proteins. ► Thirty novel Plasmodium merozoite antigens were identified. ► Seven new Pf merozoite antigens were identified for first time.